Neural Decompression by Laminectomy with Spinoplasty for Lumbar Spinal Stenosis - Pokharel, RK; Kafle, K; Pradhan, RL; Shah, LL (Nepal Orthopaedic Association Journal, 2013)
BACKGROUND Lumbar spinal stenosis is one of the common morbid conditions of adult population. Surgical intervention is recommended if conservative treatment is not effective. Aim of the surgery is to decompress neural tissues and it may vary from simple unilateral foraminotomy or laminotomy to multilevel bilateral laminectomy. Conventional laminectomy violates posterior stability and foraminotomy limits access to the neural tissues. Different techniques have been developed for adequate decompression with preservation of posterior stabilizing structures. METHODS Degenerative lumbar spinal stenosis in 22 cases was treated by laminectomy with spinous process osteotomy and re-positioning during October 2007 to August 2009. All cases had back pain with radicular pain and intermittent neurogenic claudication. Average age of the cases was 49.5 years and the average duration of symptom was 7 months. Conservative treatment was tried for 4 months. Average follow up period was 2.5 months. RESULTS Post operatively 82% of the cases were satisfied. There was no radicular pain and intermittent claudication in all cases. Persistence of back pain and numbness in lower limbs was common complaints of majority of the cases. CONCLUSION “Laminectomy with spinous process osteotomy and re-positioning” technique easily decompresses lumbar spinal stenosis with preservation of posterior osteo-ligamentous structure. DOI: http://dx.doi.org/10.3126/noaj.v1i1.8127 Nepal Orthopaedic Association Journal Vol.1(1) 2010